Data-informed Teacher Training in Islamic Schools to Impact Effective Professional Development - Nur Kholis (Islamic Studies Journal for Social Transformation, 2022)
This article challenges the assumption that teacher training programs need not to be based on data-informed decision making. It argues that such an approach neglects the contextual factors and the agency of the teachers in shaping their own professional development. Using a qualitative research method, the article presents a multiple case study of three islamic elementary schools in Pekalongan, Indonesia that have implemented data-informed teacher training programs. The findings reveal that teacher forums play a crucial role in determining the content and format of the training programs, that islamic teachers face various challenges in adapting to the digital era, and that the foundation management has a significant influence on the quality and sustainability of the training programs. The article concludes that teacher training programs should be more responsive to the needs and preferences of the teachers, rather than being imposed by mere trends and trial and error.